2004
DOI: 10.1016/j.jcrs.2004.02.083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy, predictability, and safety of LASEK for myopia and myopic astigmatism using the Technolas 217 excimer laser

Abstract: Laser-assisted subepithelial keratectomy was an effective, predictable, and safe procedure for the treatment of myopia and myopic astigmatism. Further studies are needed to determine the role of LASEK in the refractive surgery spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
(12 reference statements)
3
11
0
3
Order By: Relevance
“…Most series involving the treatment of low to moderate myopia with LASEK without prophylactic MMC describe low levels (0% to 13%) of haze formation, generally peaking at the third postoperative month and resolving by the twelfth month. 1,[3][4][5][15][16][17][18][19][20] Other series involving the treatment of moderate to high myopia report visually significant haze formation in 8% to 10% of LASEK eyes. 21 10 show that the duration of haze after LASEK depended on the severity of the haze: C1 haze resolved after 4.0 6 2.2 months, while C2 haze resolved after 5.5 6 3.3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most series involving the treatment of low to moderate myopia with LASEK without prophylactic MMC describe low levels (0% to 13%) of haze formation, generally peaking at the third postoperative month and resolving by the twelfth month. 1,[3][4][5][15][16][17][18][19][20] Other series involving the treatment of moderate to high myopia report visually significant haze formation in 8% to 10% of LASEK eyes. 21 10 show that the duration of haze after LASEK depended on the severity of the haze: C1 haze resolved after 4.0 6 2.2 months, while C2 haze resolved after 5.5 6 3.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] Partal et al 19 report 1 eye of a 27-year-old woman with a preoperative spherical equivalent of À7.25 D and an ablation depth of 178 mm who developed C2 to 3 haze that was treated with PTK and MMC with reduction of haze on subsequent visits. Camellin 1 reports an eye in which the epithelium sloughed 2 days after LASIK and the cornea later developed C4 haze, which was treated with repeat LASEK plus PTK.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that LASEK is a safe, effective, and predictable technique to correct refractive errors. [141][142][143][144][145][146] LASEK involves the use of diluted alcohol to loosen the epithelium and create an epithelial flap. There are important variations in the LASEK technique: for example, with respect to repositioning the epithelial flap after stromal ablation or discarding the epithelial flap.…”
Section: After Laser-assisted Subepithelial Keratectomy As a Re-tmentioning
confidence: 99%
“…[1][2][3][4][5][6] Despite the disadvantages of LASEK over LASIK (eg, slower visual recovery and higher postoperative discomfort), surface ablation has become the technique of choice in patients with thin corneal pachymetry, those at risk for trauma, and those with corneal surface problems such as dry eye, recurrent erosion syndrome, or epithelial basement membrane disease. 7,8 Even though excimer laser corneal refractive surgery (LASIK and surface ablation) has become highly precise, the predictability of the technique remains an issue, especially in eyes with high degrees of ametropia (either myopia 9,10 or hyperopia 11,12 ).…”
mentioning
confidence: 99%